Strengthening Indonesia’s Tax System: A Policy-Oriented Framework Based on ASEAN and OECD Case Studies - Alpha Nur Setyawan Pudjono; Ilma Nurul Rachmania (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This study investigates Indonesia’s low tax-to-GDP ratio recorded at 12.1% in 2022, far below the Asia-Pacific average of 19.3% and the OECD average of 34.0%. It aims to benchmark Indonesia’s tax compliance performance against selected ASEAN (Malaysia, Singapore, Thailand) and OECD (Denmark, Japan, Netherlands) countries to identify gaps and provide evidence-based policy recommendations. The study applies a benchmarking approach, selecting comparator countries based on similarities in economic structure and tax administration for the ASEAN group, and high-performance compliance standards for the OECD group. It is grounded in the Slippery Slope Framework and Economic Deterrence Theory to assess how trust and deterrence influence taxpayer behavior. The analysis reveals that OECD countries have leveraged digital transformation such as AI-driven audits, real-time monitoring, and integrated taxpayer services to improve compliance. In contrast, Indonesia faces persistent administrative inefficiencies, limited digitalization, and low taxpayer trust, which hamper its revenue mobilization efforts. This study offers a novel comparative perspective by integrating behavioral tax theories with policy benchmarking across diverse governance systems. It contributes actionable insights for improving Indonesia’s tax compliance through digital innovation, structured incentives, and enhanced transparency.